2016
DOI: 10.1016/j.parepi.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for shedding of Cryptosporidium spp. oocysts in dairy calves of Buenos Aires Province, Argentina

Abstract: In order to determine the prevalence and risk factors for shedding of Cryptosporidium spp. in dairy calves, a cross-sectional study was carried out in the northeastern region of Buenos Aires Province, Argentina. Fecal samples from a total of 552 calves from 27 dairy herds were collected, along with a questionnaire about management factors. Cryptosporidium spp. oocysts were detected by light microscopy using Kinyoun staining. Putative risk factors were tested for association using generalized linear mixed model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
29
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 21 publications
9
29
1
8
Order By: Relevance
“…Shedding of C. parvum oocysts was significantly associated with watery diarrhoea, mainly in calves younger than 2 weeks, which presented a higher probability of being positive than other animals; these results are in line with previous studies (Kváč et al 2006;Duranti et al 2009;Garro et al 2016). C. parvum is broadly recognised as the most pathogenic species for cattle, since it is responsible for the appearance of important neonatal diarrhoea outbreaks in farms (Santín et al 2004;Fayer et al 2006;Quílez et al 2008;Díaz et al 2010;Imre and Dărăbus 2011), although in some studies, it has also been identified as the major or the only species in healthy cattle (Santín et al 2004;Castro-Hermida et al 2011;Trotz-Williams et al 2006;Fayer et al 2007;Duranti et al 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Shedding of C. parvum oocysts was significantly associated with watery diarrhoea, mainly in calves younger than 2 weeks, which presented a higher probability of being positive than other animals; these results are in line with previous studies (Kváč et al 2006;Duranti et al 2009;Garro et al 2016). C. parvum is broadly recognised as the most pathogenic species for cattle, since it is responsible for the appearance of important neonatal diarrhoea outbreaks in farms (Santín et al 2004;Fayer et al 2006;Quílez et al 2008;Díaz et al 2010;Imre and Dărăbus 2011), although in some studies, it has also been identified as the major or the only species in healthy cattle (Santín et al 2004;Castro-Hermida et al 2011;Trotz-Williams et al 2006;Fayer et al 2007;Duranti et al 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Cryptosporidium parvum infection in calves is widespread (Brook et al 2008;Trotz-Williams et al 2008;Al Mawly et al 2015;Qi et al 2015), and also in the present study, C. parvum was, in agreement with previous reports in Argentina, the only species identified in calves (Tomazic et al 2013;Del Coco et al 2014). However, in contrast to previous studies done in Argentina, a considerably higher overall prevalence was found (Del Coco et al 2008;Tiranti et al 2011;Garro et al 2016), probably due to an additional oocysts concentration step prior to microscopic examination significantly increasing the sensitivity of oocyst detection. In the present study, the sampling fraction of calves ≤ 30 days of age was 83% (888/1073), which is the age range were C. parvum is most frequently found (Santín et al 2008;Xiao 2010;Ryan et al 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the considerable differences of overall prevalence that have been reported, corresponding dissimilarities in herd prevalence may likewise be attributed to the different sensitivities of applied diagnostic test. Accordingly, Garro et al (2016) estimated a herd prevalence of 67% (overall prevalence 16.3%) compared with 89% (overall prevalence 26.3%) in the present study. Other factors that may bias towards lower herd prevalence values, maybe the sampling of a smaller age range or a higher number of older animals (30-60 days).…”
Section: Dairy Herdcontrasting
confidence: 41%
See 1 more Smart Citation
“…Although the balance of the research seems to point to either neutral or positive effects of dam rearing on calf scours, results are mixed with respect to Cryptosporidium (see Table 2). Two of the 9 included studies reported a protective effect of the dam's presence (Kvac et al, 2006;Duranti et al, 2009), 4 reported no difference (Maldonado Camargo et al, 1998;Mohammed et al, 1999;Delafosse et al, 2015;Garro et al, 2016), and the remaining 3 (Quigley et al, 1994;Trotz-Williams et al, 2007, 2008a indicated that dam-calf contact increases the risk of infection. This lack of consensus may stem from variation in study design and outcome measurements (e.g., herd versus sample-level prevalence), in breed (dairy versus mixed dairy-beef), or in the diagnostic methods chosen.…”
Section: Calf Healthmentioning
confidence: 99%